GAMBARAN TINGKAT RISIKO KEHAMILAN DENGAN SKRINING KSPR PADA IBU HAMIL - Anggraeni, Lusiana; Theresia, Endah Marianingsih; Wahyuningsih, Heni Puji (Jurnal Kesehatan Ibu dan Anak, 2015)
Maternal mortality due to inadequate handling delivery complications, deaths can be prevented and be avoided. Early detection isimportant for predicting pregnancy complications that may occur, so it can be caught early risk factors evolve furthergestation.Maternal deaths at Sewon II PHC in 2013 increased and was ranked the fifth most pregnant women with complications inBantuI This study aims to describe the level of risk of pregnancy by screening KSPRin Sewon II onApril 2015. This type of research isdescriptive. Data in the form of primary data that is collected by direct questionnaire, and the results are expressed as a percentage(%). Subjects were 60 pregnant women at PHCof Sewon II onApril 2015. Fromthis study themajority ofmothers classified HRP andthere is potential for an obstetric emergency. Pregnant women at high risk in mothers with low education /no school, no work, poorpregnancy spacing is <2 years, while pregnant women in the age ?35 years, gave birth to more than four times, once a caesareansection, and mothers with diabetes are very risky high. From pregnancy screening results indicate that the majority of high-riskmothers need areferral systemand proper planning of deliveries for pregnantwomen at Sewon II.